Electric vehicle energy management system using National Instruments' CompactRIO and LabVIEW - Mohd, S. (2013)
This paper describes development of an electric propulsion system, energy management system (EMS) and battery management system (BMS) to convert a conventional internal-combustion-engine vehicle to a full electric vehicle. An EMS is designed, built and tested with the objective of optimizing electric power consumption of the converted electric vehicle and extend its driving range. The 'driver-assist' system monitors vehicle performance via an on-board data acquisition system. It tracks, among others, vehicle speed, motor speed, power consumption, battery and motor temperature and battery state of charge (SOC) and gives feedback in terms of suggested actions for the driver. The EMS is implemented on National Instruments' CompactRIO embedded controller, programmed on LabVIEW Real-Time software. The paper also describes development of a graphical driver interface (GDI), based on the web server function of the CompactRIO, implemented via TCP-IP connection with a tablet PC. The GDI not only offers the driver control of the EMS and in-vehicle data logging, but also remote monitoring and control of the EMS via a wireless 3G internet connection. Â© 2013 IEEE.